Analisa Faktor-Faktor yang Mempengaruhi Permintaan Perumahan Sederhana di Kota Cirebon - R Misriah Ariyanti; Adie Irwan Kusumah (Universitas Peradaban, 2018)
With increasing population growth and a high increase in people's incomes, the demand for decent housing increases. While the ability to provide housing done by the housing industry has not been able to meet the needs of existing homes. Until the year 2014, the lack of houses (backlog) reached 13, 7 million units. In an effort to reduce the backlog of housing and eliminate the slums it is necessary activities to build settlements for the community at affordable prices by people, especially low-income people. In order for the community to occupy a decent dwelling, it is necessary to make various efforts so that the number of occupancies can be increased in sufficient quantities. For that needed a strategic plan that is able to accommodate various problems that exist so that people can have or occupy a decent, quality and affordable. The research method used is a descriptive method of analysis with secondary data approach derived from documents coming from the Dinas Pemukiman dan Tata Ruang at Cirebon City and Badan Pusat Statistik (BPS) Cirebon City. The result of this research data analysis by using coefficient of determination equal to 0,997 mean influence of variable of Simplified House Price of Subsidy (X1), Income of Society (X2), Number of Population (X3), and Interest Rate of Credit Subsidy (X4) to variable Y equal to 99,7 %, while the remaining 0.3% is influenced by other variables/other factors not examined.